TEACHER STRATEGY IN DEVELOPMENT PROSOCIAL BEHAVIOR OF STUDENTS IN ELEMENTARY SCHOOL - Uus Kuswendi (PrimaryEdu : Journal of Primary Education, 2019)
Entering the digital age all information cannot be selectively displayed. Freedom in the digital age can affect the behavior patterns of students whether positive behavior or negative behavior. In an effort to prevent the emergence of negative behavior in students, it requires an environment that shapes good behavior such as prosocial behavior. Prosocial behavior really needs to be developed to prevent moral degradation. The formation of prosocial behavior can be done in a student environment such as at school. This study aims to analyze the teacher's strategy in developing students' prosocial behavior in religious-based elementary schools. The research applied a qualitative approach within the case study method. The researcher involved the teacher as the research subject located in the city of Bandung. The data collection techniques used observation, interviews, and documentation. Then, the validity of the data used triangulation techniques while the data is analyzed through thematic analysis. The finding of the research showed that there is a teacher strategy to develop prosocial behavior of students in religious based elementary schools. Giving motivation and modelling strategy are the teacher’s strategy that most widely shown.